Vascular considerations in glaucoma : current perspectives - Harris, Alon (Kugler, 2012)
PrefaceOpen angle glaucoma (OAG) is one of the leading causes of impaired vision worldwide. The pathogenesis of glaucomatous optic neuropathy remains poorly understood, and several pathogenic mechanisms are proposed to coexist. As the world population ages, OAG will become more prevalent and advances in the diagnosis and treatment of glaucomatous optic neuropathy are important to protect and improve the quality of life of our aging population.Treatment of OAG has been directed at lowering intraocular pressure (IOP) which is the only current therapeutic strategy available to patients with glauc.